DETERMINATION OF URANIUM CONCENTRATIONS IN RICE SAMPLES AVAILABLE IN THE IRAQI MARKET USING THE CR-39 DETECTOR - Al-Bayati , Auday; Alwan, Adawiya; Miran, Hussein A. (Malaysian Journal of Science, 2023)
In this study, the results of the uranium concentrations and specific activity in 10 rice samples are described using a solid-state track detector (CR-39). Samples were collected from various local Iraqi markets with different origins (Iraq, India, America, and Thailand). Our findings found that the results of uranium concentration in all studied samples are ranging from (0.55 ± 0.28 to 1.74 ± 0.31) ppm with a weighted average of (1.24 ± 0.99) ppm. Also, results demonstrate that the specific activity values of the studied samples swing between values of (6.88 ± 3.52 and 21.49 ± 3.85) Bq/Kg. The obtained results of the studied rice samples are indicated that it is less than the acceptable limit of those studies established by many organizations such as the United Nations scientific committee on the effects of atomic radiation (UNSCEAR), the international atomic energy agency (IAEA), the world health organization (WHO), and others.